Morfología funcional y hábitos alimentarios de Quetzalcoatlus (Pterosauria) - Rodríguez Prieto, Iñaqui (Coloquios de Paleontología, 1998)
The Etypochesis of LAWSON (1975) on che seavenger habits of Quetzalcaat/us is tested. by analyzing its funetional morphology and the interpretation of its habitat. Qn the base of che bilí and neck rnorphology and thc inferred mobility on che air and on ihe ground, che hypotesis seems highly improbable. We piopose an alcernative hypt4hesis of ti piscivorotis feeding habits similar té> the recent skimmcrs (Rvnchops).
Keywords: Queízalcoatíus; Pteros'auria; Funetional morpbology Habitat